2002
DOI: 10.1002/jemt.10121
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation of bone metabolism: Possible involvement of sympathetic innervation of osteoblastic and osteoclastic cells

Abstract: It has been demonstrated that human osteoblastic as well as osteoclastic cells are equipped with adrenergic receptors and neuropeptide receptors and that they constitutively express diffusible axon guidance molecules that are known to function as a chemoattractant and/or chemorepellent for growing nerve fibers. These findings suggest that the extension of axons of sympathetic and peripheral sensory neurons to osteoblastic and osteoclastic cells is required for the dynamic neural regulation of local bone metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 73 publications
5
104
0
7
Order By: Relevance
“…(52) Later, it was shown that a 2 -ARs are not restricted to presynaptic locations but also have postsynaptic locations and functions, which include regulation of body temperature, intraocular pressure, lipolysis, and pain perception. (53)(54)(55) In accordance with a previous study that identified the presence of a 2 -AR isoforms in human-derived bone cells, (2) we showed that the mRNA of the three known a 2 -AR isoforms, a 2A -, a 2B -, and a 2C -AR, are expressed in the bone of WT mice and in osteoblast-like cells derived from the mouse calvarium (MC3T3-E1 cells). In addition, we found that the mRNA expression of a 2B -AR was downregulated in a 2A /a 2C -ARKO mice compared with WT mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(52) Later, it was shown that a 2 -ARs are not restricted to presynaptic locations but also have postsynaptic locations and functions, which include regulation of body temperature, intraocular pressure, lipolysis, and pain perception. (53)(54)(55) In accordance with a previous study that identified the presence of a 2 -AR isoforms in human-derived bone cells, (2) we showed that the mRNA of the three known a 2 -AR isoforms, a 2A -, a 2B -, and a 2C -AR, are expressed in the bone of WT mice and in osteoblast-like cells derived from the mouse calvarium (MC3T3-E1 cells). In addition, we found that the mRNA expression of a 2B -AR was downregulated in a 2A /a 2C -ARKO mice compared with WT mice.…”
Section: Discussionsupporting
confidence: 91%
“…We next investigated the mRNA expression of a 2B -AR, which was shown previously to be expressed in human-derived bone cells. (2) We found that a 2B -AR is expressed in the tibias of both a 2A /a 2C -ARKO and WT mice but that its expression is 37% lower in KO animals compared with WT mice (Fig. 5A).…”
Section: Expression Of Adrenoceptors In the Skeleton And Bone Cellsmentioning
confidence: 76%
“…Bone, in particular trabecular bone, is densely innervated by sympathetic fibers (36)(37)(38), and genetic ablation of adrenergic signaling leads to a high bone mass (27,28). Like the CMSinduced depression, chronic SNS activation and sympathetic agonists inhibit bone formation mainly by decreasing osteoblast number.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts have been reported to express receptors for several neuropeptides, suggesting that they could indeed integrate multiple neuronal signals (161). Immunolabeling studies have revealed a close association between glutamate-, catecholamine-, or peptide-containing nerve fibers and osteoblasts or osteoclasts in the endosteum (162).…”
Section: Sympathetic Signalingmentioning
confidence: 99%